Physiological response of cidró to different water replacement levels in two seasons of the year - Schmidt,Denise (2017)
ABSTRACT We aimed to determine the response of cidró (Aloysia triphylla) submitted to different water replacement levels in summer and winter, in order to understand and relate the plant physiological performance under adverse weather conditions. The research was developed in a protected environment, in the city of Frederico Westphalen, Rio Grande do Sul State, Brazil. The experimental design was completely randomized, arranged in a 2x4x2 factorial scheme, two seasons of the year (summer and winter), four water availability (50, 75, 100, 125% of ETo) and two faces of leaf (abaxial and adaxial), with four replications. There were evaluated stomatal vapor diffusion resistance (s/cm), transpiration (µg/cm2/s) and leaf temperature (°C), on both faces of the leaf from 10 a.m. to 11 a.m., 1 p.m. to 2 p.m. and 4 p.m. to 5 p.m., 45 days after the beginning of the season. We concluded that the physiological response of cidró plants was influenced by water replacement levels, in a different way according to the seasons of the year. The summer season was responsible for the highest values of incident photosynthetically active radiation, leaf temperature, transpiration and stomatal vapor diffusion resistance. The reduction in water availability promoted the increase in values for stomatal resistance to vapor flow, reducing leaf transpiration rate. The incident photosynthetically active radiation, leaf temperature and transpiration showed highest values on the abaxial face of the studied species.